Patients’ Perception towards Chronic Kidney Disease and Government Policy in Nepal - Dahal, Radhika (KMC Research Journal, 2022)
This article is based on patients’ perception towards Chronic Kidney disease and government policy in Nepal. Mostly qualitative method was applied and 12 (patient with chronic Kidney disease) were taken as respondents and their perception, about policies and their suffering were recorded. Based on the findings of the research, this article argues that health is socially constructed and if the social status is better, the accessibility is higher. However, the state has health policy but it is not implemented properly because implementation is the paramount for the output. Healthy habits are social construction. Health is also socially determined. Financial burden of the patients are taken by the family. Most of the kidney donors are the relatives of the patients. The current status of the health care policy is not reachable to public.